Complement-Mediated Enhancement of Monocyte Adhesion to Endothelial Cells by HLA Antibodies, and Blockade by a Specific Inhibitor of the Classical Complement Cascade, TNT003. Issue 7 (July 2017) - Valenzuela, Nicole M.; Thomas, Kimberly A.; Mulder, Arend; Parry, Graham C.; Panicker, Sandip; Reed, Elaine F.
Abstract : Background: Antibody-mediated rejection (AMR) of most solid organs is characterized by evidence of complement activation and/or intragraft macrophages (C4d + and CD68+ biopsies). We previously demonstrated that crosslinking of HLA I by antibodies triggered endothelial activation and monocyte adhesion. We hypothesized that activation of the classical complement pathway at the endothelial cell surface by HLA antibodies would enhance monocyte adhesion through soluble split product generation, in parallel with direct endothelial activation downstream of HLA signaling. Methods: Primary human aortic endothelial cells (HAEC) were stimulated with HLA class I antibodies in the presence of intact human serum complement. C3a and C5a generation, endothelial P-selectin expression, and adhesion of human primary and immortalized monocytes (Mono Mac 6) were measured. Alternatively, HAEC or monocytes were directly stimulated with purified C3a or C5a. Classical complement activation was inhibited by pretreatment of complement with an anti-C1s antibody (TNT003). Results: Treatment of HAEC with HLA antibody and human complement increased the formation of C3a and C5a. Monocyte recruitment by human HLA antibodies was enhanced in the presence of intact human serum complement or purified C3a or C5a. Specific inhibition of the classical complement pathway using TNT003 or C1q-depleted serum significantly reduced adhesion of monocytes in the presence of human complement. Conclusions: Despite persistent endothelial viability in the presence of HLA antibodies and complement, upstream complement anaphylatoxin production exacerbates endothelial exocytosis and leukocyte recruitment. Upstream inhibition of classical complement may be therapeutic to dampen mononuclear cell recruitment and endothelial activation characteristic of microvascular inflammation during AMR. Abstract : Valenzuela et al show that HLA antibody binding to human endothelial cells in vitro, triggered complement C3a and C5a deposition that mediated monocyte recruitment, and the salutary effects of inhibiting the classical complement pathway with an anti-C1s antibody. Supplemental digital content is available in the text.